Pengaruh Pemberian Vitamin C Kombinasi Fe terhadap Peningkatan Kadar Haemoglobin pada Ibu Hamil di Puskesmas Lubuk Sanai - Choralina Eliagita; Nuril Absari; Mika Oktarina (Jurnal Kebidanan Harapan Ibu Pekalongan, 2023)
Anemia is common worldwide, especially in developing countries. Anemia is common in pregnant and lactating women. This is due to her high FE deficiency in pregnant and lactating women. This study, in the work area of the Lubuk Sanai Health Center, aimed to determine the effect of FE with vitamin C on increasing hemoglobin levels in pregnant women. A quasi-experimental study using a non-randomized Twi group pre-test and post-test design. The sampling technique in this study was to use a targeted sampling technique and 32 samples were obtained and divided into 16 control and 16 case respondents. Data collection was based on primary data by confirming Hb and secondary data by examining pregnancy register documents. The Shapiro-Wilk test was used for data analysis. Results showed that the average Hb level of mothers given vitamin C in combination with iron was her 10.362 before treatment and 11.375 after treatment, increasing by 1.013. Mean HB values in the control group were 10.288 before and 10.731 after, an increase of 0.443. At the Lubuk Sanai Health Center, giving a combination of Fe and vitamin C increases H levels in pregnant women. Puskesmas hopes to improve wellness programs to prevent anemia during pregnancy by administering a combination of vitamin C and iron tablets.